Hepatitis C virus genotype 4 in England: Diversity and demographic associations. Issue 3 (3rd September 2014) - Ngui, Siew‐Lin; Brant, Lisa; Markov, Peter V.; Tung, John‐Paul; Pybus, Oliver G.; Teo, Chong‐Gee; Ramsay, Mary E.
<x xml:space="preserve">Abstract</x> HCV strains belonging to genotype 4 may be gaining endemicity across Continental Europe but the extent of their spread in the United Kingdom is unknown. Sera referred from patients attending hospitals in England between 2004 through 2008 were characterised. A total of 243 sera carried HCV genotype 4. The most common subtypes were 4a (33%) and 4d (35%). Compared to patients infected by 4d, those infected by 4a were 20 times more likely to be Middle Eastern than English, and those infected by non‐4a/4d were older, tended to be female, and 50 or 12 times more likely to be Middle Eastern or South Asian, respectively, than English. Persons infected by 4d tended to be English rather than Middle Eastern or South Asian. One group of 4d strains clustered with strains reported from persons in Europe engaged in male homosexual activity. Surveillance of trends in the importation and subsequent spread of HCV genotype 4 and its subtypes is advocated. J. Med. Virol. 87:417–423, 2015. © 2014 Wiley Periodicals, Inc.